Amanita phalloides poisoning: one harvest, three outcomes - Pillay Mauree, A; De Maayer, T; Botes, A; Fabian, J; Etheredge, H; Duncan, EM; Botha, J (South African journal of surgery, 2019)
Summary The case study is to alert all health care workers and the public alike to the dangers of ingesting wild mushrooms. We describe an incidence of Amanita phalloides poisoning in Johannesburg, South Africa, where three different outcomes were experienced. A pregnant mother recovered with conservative management while her unborn foetus died, and her three-year-old daughter required an emergency liver transplant. We outline the clinical course, management options and principles of mushroom identification and toxicology to increase awareness of the presence of Amanita phalloides and its toxic relatives in South Africa. We highlight that early recognition, prompt treatment and referral to a transplant service is life-saving.